Nilai-Nilai Islami dalam Upacara Tradisi Mappacci - ibrahim, Nasruddin (Rihlah: Jurnal Sejarah dan Kebudayaan, 2014)
Mappacci / mappepaccing is one of a series of activities in the process of mating the Bugis Makassar known by the public as one of the conditions that must be carried by the bride or men the day before the wedding. After the traditional ceremony held mappacci the complete invitation where the relatives or the invitation that had been mandated to put in the hands of the bride and groom Pacci, the event started with the recitation of the litany or blessings on the Prophet, after officers stand litany, the procession begins by laying Pacci Anrong bunting followed by relatives and the invitation that had been given the task to put Pacci. Mappacci ceremony laden with meaning. Of a series of activities many symbols displayed value. Of those symbols, the values of Islam was much thicker either a series of activities or equipment that is used all contain Islamic values.